The Dyeability Potential of Cellulosic Fibres Using African Yellow Wood (Enantia chlorantha) (Biological Sciences - PJSIR, 2005)
The dye from African yellow tree, Enantia chlorantha, extracted by solvent extraction using acetone at a solute- solvent ratio of 1:25 was studied for its dyeability potential on cellulosic fibres. A golden yellow dye having a melting point ca 146-149 °C with 6.2% recovery was obtained. The dye was soluble in hydroxyl organic solvents. The cellulosic fibre has a greater dye uptake (26.0-23.2 mg/g) when dyed at a temperature of 80 °C than at 60 °C (22.0-21.6 mg/g). Its optimum dye-uptake, at both the temperatures, was achieved 90 min after the commencement of dyeing. However, the dyeability potential of the dye on unmordanted cellulosic fibres showed less substantivity as revealed by its low mean fastness ratings of 1.5 and 1.0 to washing and light, respectively. The tensile properties of the dyed cellulosic fibres,nevertheless, were greatly enhanced.